(untitled) (Eureka Journal of Humanities and Social Research, 2026)
Self-learning has become a central competence in contemporary education, requiring students to autonomously regulate, organize, and apply knowledge in increasingly complex academic contexts. This article proposes a Psychological Pyramid Model of Effective Self-Learning, which conceptualizes self-learning as a hierarchical and developmental process. The model integrates seven interrelated levels: foundational preparation, self-regulation and management, cognitive strategies, learning and information processing, collaboration and communication, metacognition and reflection, and academic application. Using a theoretical and analytical research design, the study synthesizes key psychological and educational theories related to self-regulated learning, cognition, and metacognition. The model demonstrates how higher-order learning outcomes depend on the systematic development of lower-level psychological capacities. The findings suggest that effective self-learning is not a single skill, but a structured system of psychological processes that evolve progressively. The proposed model offers a conceptual framework for researchers, educators, and curriculum designers seeking to support learner autonomy and sustainable academic performance.